The impact of underinsurance on bladder cancer diagnosis, survival, and care delivery for individuals under the age of 65 years. Issue 3 (18th October 2019) - Fletcher, Sean A.; Cole, Alexander P.; Lu, Chang; Marchese, Maya; Krimphove, Marieke J.; Friedlander, David F.; Mossanen, Matthew; Kilbridge, Kerry L.; Kibel, Adam S.; Trinh, Quoc‐Dien
Abstract : Background: Health insurance is a key mediator of health care disparities. Outcomes in bladder cancer, one of the costliest diseases to treat, may be especially sensitive to a patient's insurance status. Methods: The Surveillance, Epidemiology, and End Results registry and the National Cancer Data Base were used to identify individuals younger than 65 years who were diagnosed with bladder cancer from 2007 to 2014. The associations between the insurance status (privately insured, insured by Medicaid, or uninsured) and the following outcomes were evaluated: diagnosis with advanced disease, cancer‐specific survival, delay in treatment longer than 90 days, treatment in a high‐volume hospital, and receipt of neoadjuvant chemotherapy (NAC). Results: Compared with those with private insurance, uninsured and Medicaid‐insured individuals were nearly twice as likely to receive a diagnosis of muscle‐invasive bladder cancer (odds ratio [OR] for uninsured individuals, 1.90; 95% confidence interval [CI], 1.70‐2.12; OR for Medicaid‐insured individuals, 2.03; 95% CI, 1.87‐2.20). They were also more likely to die of bladder cancer (adjusted hazard ratio [AHR] for uninsured individuals, 1.49; 95% CI, 1.31‐1.71; AHR for Medicaid‐insured individuals, 1.61; 95% CI, 1.46‐1.79). Delays in treatment longer than 90 days were more likely for uninsured (OR, 1.36; 95% CI, 1.12‐1.65) and Medicaid‐insured individuals (OR, 1.22; 95% CI, 1.03‐1.44) in comparison with the privately insured. Uninsured patients had lower odds of treatment at a high‐volume facility, and Medicaid‐insured patients had lower odds of receiving NAC ( P < .001 for both). Conclusions: Compared with privately insured individuals, uninsured and Medicaid‐insured individuals experience worse prognoses and poorer care quality. Expanding high‐quality insurance coverage to marginalized populations may help to reduce the burden of this disease. Abstract : Individuals who lack adequate insurance experience relatively poor outcomes with bladder cancer. Compared with the privately insured, those who are uninsured or Medicaid‐insured have worse prognoses and receive lower quality care.